Highly efficient cycloaddition of diluted and waste CO2 into cyclic carbonates catalyzed by porous ionic copolymers. Issue 36 (February 2020) - Hui, Wei; He, Xue-Mei; Xu, Xin-Yi; Chen, Yue-Miao; Zhou, Yan; Li, Zhang-Min; Zhang, Liqi; Tao, Duan-Jian
Graphical abstract: Highlights: Mesoporous PIPs was prepared by the copolymerization of DVB with ILs. PDVB-[AlTMG]Br-0.2 showed excellent activities in cycloaddition of diluted CO2 . Various epoxides were converted into cyclic carbonates with high yields. Abstract: It is believed that porous heterogeneous materials with excellent properties are promising candidates for efficient fixation of diluted and waste CO2 . Herein, a family of mesoporous porous ionic copolymers (PIPs) was designed and prepared from the copolymerization of divinylbenzene (DVB) with vinyl-functionalized ionic liquids monomers through free radical copolymerization process. It was demonstrated that the heterogeneous PIP poly(divinylbenzene-1-allyl-tetramethylguanidinium bromide) PDVB-[AlTMG]Br-0.2 showed excellent activities in facile cycloaddition of CO2 into cyclic carbonates without using any external co-catalysts or metal additives. The results of characterizations and quantum mechanical calculations further showed that the specic hierarchical meso-macroporous structure of PDVB-[AlTMG]Br-0.2 offered the strongest binding interaction with SO and besides had a relatively good CO2 affinity, which results to the best cataltic activity for cycloaddition of CO2 . Moreover, PDVB-[AlTMG]Br-0.2 exhibited high activities and good reusability in cycloaddition of 15 % diluted CO2 with various epoxides. It is believed that our work would have a great potential in energy-effective fixation of industrial combustion CO2 into high-value organic carbonates.